A bi-level market-clearing for coordinated regional-local multi-carrier systems in presence of energy storage technologies. (December 2020) - Nasiri, Nima; Sadeghi Yazdankhah, Ahmad; Mirzaei, Mohammad Amin; Loni, Abdolah; Mohammadi-Ivatloo, Behnam; Zare, Kazem; Marzband, Mousa
Highlights: Proposing a decentralized mechanism for coordinated local-regional energy systems. Using an iteration based two-step framework to solve the introduced model. Including energy storage resources in the integrated local-regional energy systems. Applying a stochastic approach to handle the uncertainties of the integrated system. Presenting a linearized gas network model considering linepack. Abstract: A multi-energy system (MES) provides greater flexibility for the operation of different energy carriers. It increases the reliability and efficiency of the networks in the presence of renewable energy sources (RESs). Various energy carriers such as power, gas, and heat can be interconnected by energy storage systems (ESSs) and combined heat and power units at different levels (e.g., within a region or a local). Non-coordinated optimization of energy systems at local and regional levels does not verify the whole optimal operation of systems since the systems are operated without considering their interactions with each other. One of the most famous sources of flexibility is ESSs. Hence, this paper presents a stochastic decentralized approach to evaluate the impact of ESSs on regional-local MES market-clearing within a bi-level framework. On the regional level, the economic interaction between the electricity and natural gas (NG) systems is carried out by a centralized system operator (CSO). In addition, coordination between various energy carriers is implemented by the energy hub operator at the local level. To ameliorate the flexibility of the NG system in the regional MES, the linepack model of gas pipelines has been considered. Local MES modeling is performed through multiple input/output ports using a linear energy hub model. The proposed model is a mixed-integer linear programming (MILP), which is solved by CPLEX solver in GAMS software.